Impact on Base Population Density and Hunter Performance of Stocking with Pen-Raised Bobwhite - Keith Sexson Jr.; James A. Norman (National Quail Symposium Proceedings, 2017)
In 1962, the Kansas Fish and Game Commission initiated an investigation to determine the effect of semiannual releases of pen-raised bobwhite quail (Colinus virginianus) on population densities of native wild quail populations, on availability of birds to hunters, and on hunter success. Stocking during spring resulted in 7% fewer birds in the fall population on the stocked area than on the control area. Stocking during fall resulted in 14% more birds, at the time hunting season began, on the stocked area than on the control area. Neither of these differences were statistically significant, and it is concluded that there was no significant difference attributable to stocking between population densities of stocked and control areas. On the stocked area, however, there was a significant net increase of 25% in population density between the fall census period and the preseason census period. It is concluded that the density-depressing influence of spring stocking combined with the density-elevating influence of fall stocking, on the stocked area, produced a significant increase, attributable to stocking, between the population density preceding fall release and the population density preceding the hunting season. It is further concluded that in the comparison of preseason population densities for the treatment and control areas, the depressing effect of spring stocking and the elevating effect of fall stocking resulted in a treatment-area population that was significantly larger than that found on the unstacked control area. Some pen-raised birds established themselves as a part of the population on the stocked area, but there was not a proportional increase in population density. There were fewer native quail on the area when treated with semiannual stocking than when under control condition. The difference in density of native birds between stocked and control areas was not statistically significant. Stocking significantly increased hunter success by 30% and 35% on areas in Cherokee and Linn Counties, respectively, but the number of coveys flushed per hour was not significantly increased by stocking pen-raised quail.